The Impact of Liquidity, Profitability, Leverage, and Cash Flow on Financial Distress in Wholesale Sector Companies Listed on The IDX from 2016-2019 - Alfia, Lilik; Hizazi, Achmad; Mansur, Fitrini (Faculty of Economics and Business Universitas Jambi, 2024)
This research aims to examine the effect of liquidity, profitability, leverage and cash flow on financial distress in large trading sub-sector companies listed on the Indonesia Stock Exchange in 2016-2019. This research was conducted by purposive sampling method. Data collection techniques using secondary data. The financial distress variable is proxied using the Altman Z-Scored formula. Data obtained from large trading subsector companies listed on the Indonesia Stock Exchange (IDX) from 2016-2019 using the Multiple Linear Regression method using SPSS 23. The results of this study indicate that: (1) liquidity has an effect on financial distress (2) profitability has an effect on financial distress, high profitability indicates the company is able to maximize its assets (3) leverage has no effect on financial distress, even though the company has a lot of debt to finance its operations (4) cash flow has no effect on financial distress. This study contributes to the expanding corpus of research on corporate financial distress. The results are consistent with current financial theories that highlight the importance of profitability and liquidity as critical markers of a business's financial health. On the other hand, the lack of discernible impact from cash flow and leverage. These findings support further investigation into qualitative and contextual elements